2008
DOI: 10.1002/art.23401
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of temporomandibular joint arthritis at disease onset in children with juvenile idiopathic arthritis, as detected by magnetic resonance imaging but not by ultrasound

Abstract: Objective. To determine the prevalence of temporomandibular joint (TMJ) disease in a cohort of children with new-onset juvenile idiopathic arthritis (JIA), and to compare magnetic resonance imaging (MRI) with ultrasound (US) for the detection of acute and chronic changes of TMJ arthritis.Methods. Between January 2005 and April 2007, children with newly diagnosed JIA were prospectively evaluated for TMJ arthritis. Prior to imaging, jaw pain and disability were assessed with questionnaires and physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
254
3
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(298 citation statements)
references
References 22 publications
17
254
3
24
Order By: Relevance
“…It is usually painless and even minor radiographic changes of the TMJ have been associated with disruption in mandibular growth and a number of other craniofacial changes 1 . Recently, magnetic resonance imaging (MRI) evaluations have proven to have much greater sensitivity to detect arthritis compared to ultrasound, and placed the prevalence of TMJ arthritis in this population between 63% and 75% 2,3 . Due to this high prevalence, patients with JIA frequently receive contrast-enhanced MRI scans of the TMJ as a standard evaluation for arthritis in several clinical centers.…”
Section: To the Editormentioning
confidence: 99%
“…It is usually painless and even minor radiographic changes of the TMJ have been associated with disruption in mandibular growth and a number of other craniofacial changes 1 . Recently, magnetic resonance imaging (MRI) evaluations have proven to have much greater sensitivity to detect arthritis compared to ultrasound, and placed the prevalence of TMJ arthritis in this population between 63% and 75% 2,3 . Due to this high prevalence, patients with JIA frequently receive contrast-enhanced MRI scans of the TMJ as a standard evaluation for arthritis in several clinical centers.…”
Section: To the Editormentioning
confidence: 99%
“…The reported frequency of TMJ involvement ranges in the literature from 17% to 87%, depending on the population investigated, the subtypes represented, and the radiologic method by which involvement is diagnosed. [5][6][7][8][9][10][11][12][13][14] Only one study reported the incidence of TMJ involvement in all subtypes of JIA. 6 The most important site of growth of the mandible in the vertical and sagittal direction is located on the articular surface of the condylar head.…”
Section: Introductionmentioning
confidence: 99%
“…6 The most important site of growth of the mandible in the vertical and sagittal direction is located on the articular surface of the condylar head. [12][13][14][15] During nor- mal growth of the dentomaxillary complex, the vertical dimension increases more than the sagittal dimension does. Arthritis of the TMJ results in reduced mandibular growth and subsequent alteration in dental occlusion and may even affect total craniofacial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with such changes have major impact in their quality of life, with impairment of their functional activities and, very often, with mood and sleep changes 3 . TMD prevalence in general population varies from 10% to 70%, being more frequent among females between 20 and 40 years of age 3,4 . Among joint TMD, reducing and nonreducing disk displacements and osteoarthritis are more frequent changes in patients looking for treatment [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…TMD prevalence in general population varies from 10% to 70%, being more frequent among females between 20 and 40 years of age 3,4 . Among joint TMD, reducing and nonreducing disk displacements and osteoarthritis are more frequent changes in patients looking for treatment [3][4][5] . Different approaches have been proposed to control such disorders, among them conservative treatments (drugs, physiotherapy, stabilizing and repositioning occlusal devices, guidelines), minimally invasive treatments (sodium hyalorunate or corticosteroid infiltrations and arthrocentesis), and invasive treatments (arthroscopy, arthroplasty, arthrotomy) [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%